Abundance of fungi on rice straw compost and husk biochars by in-vitro heavy metals mycosorbent - NURUL PUSPITA PALUPI; RORO KESUMANINGWATI; ARYA BAYA SRIPATI; ESTI HANDAYANI HARDI; FAHRUNSYAH FAHRUNSYAH; DWI ERMAWATI RAHAYU; RUDY AGUNG NUGROHO; SURYA DARMA; SURIA DARMA IDRIS (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Palupi NP, Kesumaningwati R, Sripati AB, Hardi EH, Fahrunsyah, Rahayu DE, Nugroho RA, Darma S, Idris SD. 2025. Abundance of fungi on rice straw compost and husk biochars by in-vitro heavy metals mycosorbent. Biodiversitas 26: 1983-1990. In Samarinda, all paddy fields are contaminated by heavy metals with concentrations exceeding the critical threshold and has disrupted human health and worsened the quality of the agroecosystem of rice fields. This study aims to evaluate the effectiveness of compost and biochar application in absorbing heavy metals in paddy field soil in Samarinda. The research method involves the application of compost, biochar, and their combination on paddy field soil contaminated with heavy metals using incubation experiment with 5 treatments and 4 replications, completely randomized design, and measured parameters (pH, Fe, Zn Cd, and Aspergillus niger). The results indicate that the use of compost significantly increases the population of A. niger and reduces the concentration of heavy metals such as Fe, Zn, and Cd in the soil. On the other hand, biochar has also proven effective in reducing the content of heavy metals, supported by its high adsorption capacity. The combination of compost and biochar shows better results compared to individual applications, indicating synergy between organic nutrients and adsorption capabilities. The correlation between the population of A. niger and heavy metals demonstrates a significant relationship, confirming the role of microbes in soil bioremediation. The practical implication of this research underscores the importance of organic fertilizer use in reducing heavy metal contamination, supporting sustainable agriculture, and reducing dependence on synthetic chemicals. Future research is recommended to further understand the mechanisms of bioremediation and soil microbe interactions in this context. In conclusion, the application of compost and biochar offers a holistic approach to effectively address heavy metal contamination issues, enhance soil quality, and support environmentally friendly agriculture.